D. Giovanni Francesco Gemelli Careri and the aboriginals of the Philippine archipelago - Zell, Reg. (Bures-sur-Yvette, France : Reg Zell, 2021)
Summarizes Gemelli Careri's travels leading to his voyage in the Philippines and descriptions of aboriginals of Luzon, Panay, Mindanao, and Bataan.
English.
Keywords: Gemelli Careri, Giovanni Francesco, -- 1651-1725.; Voyages around the world -- Early works to 1800.; Indigenous peoples -- Philippines; Ethnology -- Philippines; Material culture -- Philippines; Philippines -- Description and travel; Philippines -- Historiography; Philippines -- Antiquities